2016
DOI: 10.1002/wsb.638
|View full text |Cite
|
Sign up to set email alerts
|

Diseases associated with translocation of captive cervids in North America

Abstract: The privatization of captive cervids, with associated interstate movement of cervids, poses a substantial health risk to native free-ranging wildlife and domestic animals in North America. Captive cervid operations provide an avenue for transmission of diseases such as chronic wasting disease that could have significant impact on wild cervid populations. In addition, other infectious parasites and pathogens that are potentially associated with captive cervid operations and translocation include, but are not li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Although its definitive host is the white-tailed deer, a number of studies have confirmed that P. tenuis can parasitize many different hosts, including elk, moose ( Alces alces ), llamas ( Lama glama ), alpacas ( Vicugna pacos ), goats ( Capra hircus ), cattle ( Bos taurus ), horses ( Equus caballus ), bison ( Bison bison ), sika deer ( Cervus nippon ) and guinea pigs ( Cavia porcellus ; Anderson, 1972; Lankester, 2001, 2010; Weiss et al ., 2008; Whitehead and Bedenice, 2009; Gerhold et al ., 2010; Tanabe et al ., 2010; Mitchell et al ., 2011; Southard et al ., 2012; Dobey et al ., 2014; Gerhold and Hickling, 2016). To date, the majority of these studies have focused on genetic confirmation of host infection and identification of morphologically indistinguishable dorsal-spined larvae in Elaphostrongyline species (Gajadhar et al ., 2000; Kutz et al ., 2001; Gerhold et al ., 2010; Dobey et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its definitive host is the white-tailed deer, a number of studies have confirmed that P. tenuis can parasitize many different hosts, including elk, moose ( Alces alces ), llamas ( Lama glama ), alpacas ( Vicugna pacos ), goats ( Capra hircus ), cattle ( Bos taurus ), horses ( Equus caballus ), bison ( Bison bison ), sika deer ( Cervus nippon ) and guinea pigs ( Cavia porcellus ; Anderson, 1972; Lankester, 2001, 2010; Weiss et al ., 2008; Whitehead and Bedenice, 2009; Gerhold et al ., 2010; Tanabe et al ., 2010; Mitchell et al ., 2011; Southard et al ., 2012; Dobey et al ., 2014; Gerhold and Hickling, 2016). To date, the majority of these studies have focused on genetic confirmation of host infection and identification of morphologically indistinguishable dorsal-spined larvae in Elaphostrongyline species (Gajadhar et al ., 2000; Kutz et al ., 2001; Gerhold et al ., 2010; Dobey et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife translocation remains a popular tool for re-establishing declining or extirpated species and the science guiding the application of this tool has progressed (Seddon et al ., 2007, 2012; Batson et al ., 2015). Despite increased knowledge and improved procedures, translocations, which involve the introduction of naive hosts into new environments with novel pathogens, invariably pose an increased risk of disease (Ballou, 1993; Viggers et al ., 1993; Gerhold and Hickling, 2016). It is possible to carefully consider and mitigate the disease risk for the translocated organisms at capture, captivity and pre-release stages, but the novel host−pathogen interactions that result post-release are often problematic and difficult to predict in advance (Cunningham, 1996; Ewen et al ., 2012; Hartley and Sainsbury, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the number of individual animals that were sourced from captive situations decreased by 157,542 individual animals in 2016 representing a 13.2% decrease in this type of trade globally compared to 2012. The benefits and impacts of captive breeding for supplying commercial trade in wildlife on human health are both poorly understood and subject to debate (for example see Ballou, 1993;Kock et al, 2010;Gerhold and Hickling, 2016). On one hand, captive breeding at registered facilities provides relevant health authorities with an opportunity to better monitor the disease risks that this type of trade poses to the public both now and in the future.…”
Section: Rankmentioning
confidence: 99%
“…On one hand, captive breeding at registered facilities provides relevant health authorities with an opportunity to better monitor the disease risks that this type of trade poses to the public both now and in the future. However, if managed poorly, captive breeding can also involve large numbers of animals in poor welfare conditions which are a likely source of zoonotic diseases (for example see Ballou, 1993;Kock et al, 2010;Gerhold and Hickling, 2016).…”
Section: Rankmentioning
confidence: 99%
“…Numerous cases exist in human medicine of iatrogenic pathogen transmission between patients and health care workers due to poor biosecurity practices [ 5 7 ]. Many pathogens are highly contagious, hence practices such as co-housing animals could result in transmission between infected and uninfected individuals [ 8 , 9 ]. Some pathogens also can be shed through the skin [ 10 , 11 ], hence handling different individuals without changing gloves could facilitate transmission.…”
Section: Introductionmentioning
confidence: 99%